Differences Effectiveness of Behavioral Counseling Modeling Technique with Aversi Technique to Self Endurance - I Dewa Gede Agung Permana Putra; Dewi Arum MWP; I Ketut Dharsana (Bisma The Journal of Counseling, 2017)
The purpose of this research is to know the effectiveness of behavioral counseling model of modeling technique to experiment class I with students given conventional treatment to stabilize Self Endurance students of SMK N 2 Singaraja, to know effectiveness of behavioral counseling model aversi technique to experiment class II with students given treatment conventionally to stabilize Self Endurance student of SMK N 2 Singaraja, to know the difference of effectiveness of behavioral counseling model of modeling technique with aversi technique to Self Endurance of SMK N 2 Singaraja students. The process of collecting data in this study using observation sheet, interview sheet, diary and Self Endurance questionnaire. This research is a quasi research ("Quasi Experiment"), data analysis method used is t-test. From this research, modeling technique is more effective than the aversion model of behavioral counseling model in stabilizing Self Endurance of class X students of SMK Negeri 2 Singaraja.